The “open family firm”: openness as boundary work in family enterprises - Frank Lambrechts; Jolien Huybrechts; Alfredo De Massis; Erik E. Lehmann (Small Business Economics, 2022)
Openness" has become an established norm in the contemporary business environment. However, despite the crucial importance of boundaries and boundary work in organization and management theory, openness—as opening up boundaries of family firms and entrepreneurial families in collaborating with external actors—has received only nascent attention in the family business domain. We introduce the notion of openness in the family business field. Drawing on the organizational boundary and family business literatures, we develop a conceptual framework of family firm openness as boundary work and examine and discuss the drivers, mechanisms, and consequences of openness in family enterprises. Then, drawing on this framework, we set out an agenda for future research that will contribute to a better understanding of openness, boundaries, and boundary work in family firms and entrepreneurial families. We conclude by discussing some contemporary examples of research on the "open family firm.
Keywords: M14; D8; L14; L21; 330; Family business; Openness; Boundary work; Organizational boundaries; Social capital; Social networks; Open innovation; Ecosystems; Collaboration; Entrepreneurial family